The natural course of gastric intestinal metaplasia in Turkish patients: A single-center observational cohort study - ÇELİKEL, ÇİĞDEM; DEMİRTAŞ, COŞKUN ÖZER; GÜNDÜZ, FEYZA (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Gastric intestinal metaplasia (GIM) is considered as a predisposing lesion for the development of gastric cancer and is recommended to be kept under surveillance in designated intervals. We aimed to assess the natural course of GIM in a large Turkish cohort. Materials and Methods: We retrospectively reviewed findings from pathology reports of gastric biopsies conducted between 2011 to 2018 to reveal patients diagnosed with solitary GIM in their index pathology report. Progression of GIM was pre-defined as; lowgrade dysplasia (LGD), high-grade dysplasia (HGD), or gastric malignancy. Results: The median follow-up period of the study population was 34 (12-128) months. Out of 109 patients with GIM at the entry, 54 (49.6%) patients had stable GIM, whereas 53 (48.6%) cases had no signs of GIM at their final endoscopy. Only two (1.8%) patients progressed to LGD, but no HGD or malignancy was detected in the follow-up. Conclusion: Although, considered as a premalignant lesion and offered surveillance globally, progression of GIM was very low in a large Turkish cohort. Further prospective studies in larger cohorts are required to enlighten the obscure strategies in the surveillance of gastric malignancy.
Keywords: Gastric intestinal metaplasia; Gastric cancer; Dysplasia; Surveillance; HELICOBACTER-PYLORI ERADICATION; PREMALIGNANT LESIONS; RISK